Specific Plant Mycorrhizal Responses Are Linked to Mycorrhizal Fungal Species Interactions - Guo, Xin; Wang, Ping; Wang, Xinjie; Li, Yaoming; Ji, Baoming (Frontiers in Plant Science, 2022)
Effects of arbuscular mycorrhizal fungi (AMF) on plants span the continuum from mutualism to parasitism due to the plant-AMF specificity, which obscures the utilization of AMF in the restoration of degraded lands. Caragana korshinskii, Hedysarum laeve, Caragana microphylla, and Poa annua are the most frequently used plants in revegetation in Kubuqi desert, China, and the influence of AMF on their re-establishment remains to be explored further. Here, using a greenhouse experiment, we tested the plant-AMF feedbacks between the four plant species and their conspecific or heterospecific AMF, retrieved from their rhizosphere in the Kubuqi desert. AMF showed beneficial effects on plant growth for all these plant-AMF pairs. Generally, the biomass of C. korshinskii, H. laeve, C. microphylla, and P. annua were increased by AMF by 97.6%, 50.6%, 46.5% and 381.1% relative to control, respectively. In addition, the AMF-plant specificity was detected. P. annua grew best, but C. microphylla grew worst with conspecific AMF communities. AMF community from P. annua showed the largest beneficial effect on all the plants (with biomass increased by 63.9-734.4%), while the AMF community from C. microphylla showed the least beneficial effect on all the plants (with biomass increased by 9.9%-59.1%), except for P. annua (a 292.4% increase in biomass). The magnitude of AMF effects on plant growth were negatively correlated with the complexity of the corresponding AMF co-occurrence networks. Overall, this study suggests that AMF effects on plant growth varies due to plant-AMF specificity. We also observe the broad-spectrum benefits of the native AMF from P. annua, which indicates its potential utilization in the restoration of the desert.